Regionalism and Human Protection : Reflections from Southeast Asia and Africa. - Hunt, Charles T. (BRILL, 2018)
This book provides a detailed examination of how norms concerning human rights, civilian protection and prevention of mass atrocities have fared in the regions of Southeast Asia and Africa. Originated as a spin off of the journal GR2P (vol. 8/2-3, 2016), it has been enriched with new chapters and revised contents, which contrast the different experiences of those regions and investigates the expression of human protection norms in regional organisations and thematic policy agendas as well as the role of civil society mechanisms/processes. Hunt and Morada have brought together scholar-practitioners from across the world. The collection identifies a range of insights that provide rich opportunities for south-south exchange and mutual learning when it comes to promoting and building capacity for human protection at the regional level.